1990
DOI: 10.1103/physreva.42.7271
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of simple magnetic hole systems

Abstract: Experiments on a system of two magnetic holes (nonmagnetic microspheres in ferrofluid) subject to a rotating magnetic field show various types of behavior depending on the driving frequency. For two spheres (holes) mechanically bound together the stable rotation mode at low frequencies is replaced above a critical frequency by a mode with alternating rotation directions. This is described by simple nonlinear equations, and simulations show good quantitative agreement with the experiments. For two free spheres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 10 publications
2
58
1
Order By: Relevance
“…It was shown that for frequency above the wire undergoes an hydrodynamic instability between two rotation regimes [32,33]. In Regime I, the wire rotates at the same frequency as the field, whereas in Regime II it is animated of asynchronous back-and-forth motions.…”
Section: -Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that for frequency above the wire undergoes an hydrodynamic instability between two rotation regimes [32,33]. In Regime I, the wire rotates at the same frequency as the field, whereas in Regime II it is animated of asynchronous back-and-forth motions.…”
Section: -Theoretical Backgroundmentioning
confidence: 99%
“…2 illustrate typical temporal evolutions of the wire orientation for viscous (a, b), elastic (c, d) and viscoelastic (e, f) cases. The red lines indicate the average angular velocity Ω = [18,32,33]. For viscous and viscoelastic fluids, Ω is positive whereas it is zero for an elastic solid.…”
Section: -Theoretical Backgroundmentioning
confidence: 99%
“…The force on each nonmagnetic particle in a magnetic field gradient is proportional to the product of the net fluid magnetization ͗M ជ ͘, with the fluid volume V displaced by the nonmagnetic particle (14,15).…”
Section: Basic Principles Of Particle Assembly and Transportmentioning
confidence: 99%
“…Magnetic forces on nonmagnetic particles are transmitted through a fluid dispersion of magnetic nanoparticles, such as commercially available ferrofluid. Previously, magnetic forces have been exploited to assemble nonmagnetic particles into somewhat regular structures within the bulk of the fluid, but little control over the assembly process was achieved (14,15). In the present work, we employ magnetization patterns as a template for producing reprogrammable magnetic field maps, which leads to improved control over particle assembly and manipulation.…”
mentioning
confidence: 99%
“…This orientation dependence of the dipolar interactions can be further exploited by using time-dependent magnetic fields with large Mason number [5] that vary on a time scale too fast for the colloids to relax to their instantaneous equilibrium position [3,6,7]. The colloids therefore experience the time-averaged dipolar interactions.…”
Section: Introductionmentioning
confidence: 99%